Strategi Komunikasi Pemasaran dalam Meningkatkan Penjualan melalui Instagram @Foofie.Rissole - Rizky, Elvina; Saragih, M. Yoserizal; Abidin, Syahrul (Comit: Communication, Information and Technology Journal, 2024)
Pematang Panjang State Elementary School 15, Sijunjung District, Sijunjung Regency in Islamic Religious Education subjects where in these subject teachers still often use the lecture method where students only listen to the teacher during learning, however teachers also combine the lecture method with other learning methods such as discussion methods and question and answer. This research was carried out at Pematang Panjang State Elementary School 15, Sijunjung District, Sijunjung Regency in the subject of Islamic Religious Education where in this subject teachers still often use the lecture method where students only listen to the teacher during learning, however teachers also combine the lecture method with other learning methods., such as discussion and question and answer methods. This research shows that this lecture method is able to enliven the class atmosphere and is able to increase interest in learning and also improve student learning outcomes for students at State Elementary School 15 Pematang Panjang, Sijunjung District, Sijunjung Regency.